Metastatic Breast Carcinoma on Diffuse Spine Metastatic Process Using Augmented Exoskeleton Cement: Proposing a New Technique - Tjokorda Mahadewa GB (Journal of Global Pharma Technology, 2017)
Metastatic breast cancer (MBC) to the cervicothoracic area of the spine is very rare cases. In this case report, we describe a case for this rare lesion. Case: a thirty-nine-year-old female with a history of weakness of the legs and pain in the upper back spine came to the hospital with history of breast biopsy with result of adenocarcinoma and positive long tract signs. On whole-spine MRI, it is shown the bone metastatic process on C5-7, T3, T5-7, T9-10 with bony destructions and extradural mass around T5-7 and T9-10. Two stages of surgery were planned for this patient. The first operation was addressed to cervical metastatic process through the posterior approach, in the form of a cervical fusion with laminectomy biopsy. The second step was via posterior approach for thoracic decompression and fusion. Since the Karnovsky score was 60 and single step surgery was chosen, led to cervicothoracic decompression fusion at single stage using augmented exoskeleton cement technique. During follow-up, the patient was neurologically improved on the both legs function significantly, though gait was still tolerable and recovery program was still ongoing in outpatient department. MBC treatment for long spine involved lesions can also be handled via a single posterior approach with good results especially for case with cervicothoracic metastatic process.Keywords: Metastatic breast cancer, Posterior approach, Cervicothoracic fusion, Exoskeleton.